2020
DOI: 10.1111/jdv.16966
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis severity: commonly used clinical thresholds may not adequately convey patient impact

Abstract: Background Psoriasis severity is usually evaluated using quantitative and qualitative measures, including per cent body surface area (BSA) involvement, the Psoriasis Area and Severity Index (PASI) and the Dermatology Life Quality Index (DLQI), a patient‐reported questionnaire. However, standardized definitions for psoriasis severity categories have not been well established. A PASI of 10 or 12 has remained the minimal severity threshold defining eligibility for psoriasis treatments. In the present study, the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Besides, we found that PASI and DLQI have almost no correlation between values of DLQI >10 from our real-world data (r=0.16, P<0.001), which in accordance with one study reported that patients with DLQI >10 also reported PASI mostly lower than 10. 8 However, there are also some studies that reported a good correlation between PASI and DLQI. The possible reason for this is that only patients with PASI >10 were allowed to enter clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, we found that PASI and DLQI have almost no correlation between values of DLQI >10 from our real-world data (r=0.16, P<0.001), which in accordance with one study reported that patients with DLQI >10 also reported PASI mostly lower than 10. 8 However, there are also some studies that reported a good correlation between PASI and DLQI. The possible reason for this is that only patients with PASI >10 were allowed to enter clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“… 7 However, in light of existing literature, PASI was not a comprehensive indicator of disease severity, and the importance of the DLQI is underestimated. 8 If the patient was assessed solely based on PASI, according to the “Rule of Tens”, patients were classified as “mild-to-moderate”. They only received topical therapy, even if their DLQI showed severe effects.…”
Section: Introductionmentioning
confidence: 99%
“…Mahil et al ( 20 ) recently stated that PASI ≤2 and PGA clear/almost clear are relevant for treat to target strategies. In our opinion however, not only disease activity, but also QoL, should be taken into account, as it might differ among patients as to which PASI scores are acceptable ( 21 ). Therefore a low DLQI was a prerequisite, apart from PASI.…”
Section: Discussionmentioning
confidence: 99%
“…Disease severity is usually assessed clinically utilizing tools like PASI, which has some limitations and subjectivity. Clinician prescribes the treatment based on the severity of PsO, aiming that patient achieves longer remission period and better quality of life 7 …”
Section: Introductionmentioning
confidence: 99%
“…Clinician prescribes the treatment based on the severity of PsO, aiming that patient achieves longer remission period and better quality of life. 7 Biomarkers for diagnosis and prognosis of PsO help establish disease severity and monitor the therapy. 8 Studies have demonstrated that Th1/Th2 and Th17/T-reg cells and their associated cytokines have significant roles in the pathogenetic process of PsO.…”
mentioning
confidence: 99%